2014
DOI: 10.1136/bcr-2013-202688
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular block related to liposomal amphotericin B

Abstract: Atrioventricular block can occur in normal children, young adults or athletes. It is also associated with underlying heart disease or occurs as a drug adverse effect. Amphotericin B is used in the treatment of invasive fungal infections. Cardiac toxicity is a rare adverse reaction. We report the case of a 9-month girl, admitted in the paediatric intensive care unit with cytomegalovirus pneumonitis. During hospitalisation the patient developed a systemic fungic infection and was medicated with liposomal amphote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Since then, a review of the literature has identified nine reports of anaphylaxis or cardiac toxicity attributed to LAmB (Table 1). Of note, all the cases of cardiac toxicity appeared to be dose and time dependent (occurring only after multiple sequential doses) and were associated with hyperkalaemia [8][9][10][11], for which amphotericin B has been assigned a "black box warning, " however our case was normokalaemic at the time of event. Three of the reported cases of LAmB anaphylaxis were administered conventional amphotericin B either prior to or following LAmB without reaction [12][13][14], suggesting allergic reaction to the liposome or other excipients.…”
Section: Discussionmentioning
confidence: 94%
“…Since then, a review of the literature has identified nine reports of anaphylaxis or cardiac toxicity attributed to LAmB (Table 1). Of note, all the cases of cardiac toxicity appeared to be dose and time dependent (occurring only after multiple sequential doses) and were associated with hyperkalaemia [8][9][10][11], for which amphotericin B has been assigned a "black box warning, " however our case was normokalaemic at the time of event. Three of the reported cases of LAmB anaphylaxis were administered conventional amphotericin B either prior to or following LAmB without reaction [12][13][14], suggesting allergic reaction to the liposome or other excipients.…”
Section: Discussionmentioning
confidence: 94%
“…Different formulations reflect different pH, viscosity, surface tension, and osmolality. Amphotericin B rarely causes cardiac involvement, but when it does, critical cardiomyopathies and arrhythmias may develop [ 111 , 112 ]. The above new drug preparations may help reduce toxic side effects, especially in bedridden patients with frequent cardiovascular comorbidities.…”
Section: Myocardial Toxicity Induced By Antibiotics and Possible Reme...mentioning
confidence: 99%
“…However in our patient, blood pressure was normal at the time of the STEMI. Other post‐marketing cardiotoxicity‐related events include reversible dilated cardiomyopathy, atrioventricular block and ventricular arrhythmias, including torsades de pointes …”
Section: What Is New and Conclusionmentioning
confidence: 99%